Comparing Herzberg and Maslow: Work Motivation in Modern Organizations - Aep Saepudin; Siti Rahmayanti (LifeSciFi, 2025)
Employee motivation remains a central concern in human resource management, particularly amid evolving work dynamics such as generational shifts, remote work, and digital transformation. Two prominent theories Maslow’s Hierarchy of Needs and Herzberg’s Two-Factor Theory have long guided organizational strategies but require renewed evaluation in light of current challenges. This study aims to analyze and compare both models to assess their relevance in contemporary organizational contexts. A Systematic Literature Review (SLR) was employed to examine scholarly sources from the past two decades, focusing on the theoretical structures, implementation practices, and contextual adaptability of both models. The findings reveal that while Maslow offers a tiered framework of human needs, its rigid hierarchy is often misaligned with modern employee preferences that prioritize self-actualization and purpose from early career stages. Herzberg’s model, emphasizing job design and intrinsic motivators, is more adaptable but may oversimplify motivational drivers across cultures and roles. The study concludes that a hybrid motivational strategy integrating Maslow’s foundational understanding of needs with Herzberg’s focus on job enrichment can enhance engagement, satisfaction, and retention. Organizations must customize motivational practices using technology and employee analytics to align with diverse and evolving workforce expectations.